2019
DOI: 10.3389/fmicb.2019.02436
|View full text |Cite
|
Sign up to set email alerts
|

FNR-Dependent RmpA and RmpA2 Regulation of Capsule Polysaccharide Biosynthesis in Klebsiella pneumoniae

Abstract: Fumarate nitrate reduction regulator (FNR) is a direct oxygen-responsive transcriptional regulator containing an iron-sulfur (Fe–S) cluster. During anaerobic growth, the [4Fe–4S] cluster in FNR (holo-FNR) binds specifically to DNA, whereas exposure to oxygen results in the loss of its DNA-binding activity via oxidation of the [4Fe–4S] cluster. In this study, we aimed to investigate the role of FNR in regulation of capsular polysaccharide (CPS) biosynthesis, serum resistance, and anti-phagocytosis of K. pneumon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
(87 reference statements)
1
6
0
Order By: Relevance
“…The capsule polysaccharide production has three transcription units ( orf1-2 , orf3-15 , and orf16-17 ) in Kp, among which two are directly influenced by rmpA , while one is affected by rmpA2 . The deletion of rmpA and rmpA2 leads to decreased capsular polysaccharide under anaerobic conditions ( Lin et al, 2019 ), which is also observed in the present study. Hence, CR-hvKp that lacks rmpA and rmpA2 lacks hypermucoviscous phenotype due to decreased capsular polysaccharide production.…”
Section: Discussionsupporting
confidence: 90%
“…The capsule polysaccharide production has three transcription units ( orf1-2 , orf3-15 , and orf16-17 ) in Kp, among which two are directly influenced by rmpA , while one is affected by rmpA2 . The deletion of rmpA and rmpA2 leads to decreased capsular polysaccharide under anaerobic conditions ( Lin et al, 2019 ), which is also observed in the present study. Hence, CR-hvKp that lacks rmpA and rmpA2 lacks hypermucoviscous phenotype due to decreased capsular polysaccharide production.…”
Section: Discussionsupporting
confidence: 90%
“…To further evaluate the anti-virulence activity of VC, the transcriptional responses of both strains KP1088 and hvKP3 in the presence of VC at 4 mg/mL were determined. The rmpA and rmpA2 gene encode capsule biosynthesis and hence the mucoid phenotype in hvKP strains ( Lin et al., 2019 ). According to previous studies, strain KP1088 carried both the rmpA and rmpA2 genes, and that strain hvKP3 carried the rmpA2 gene only ( Gu et al., 2018 ; Zhang et al., 2016a ).…”
Section: Resultsmentioning
confidence: 99%
“…Plasmid pMS3802-CTXM-vir also encoded some virulence-related genes such as the ferric aerobactin iucABCD and aerobactin receptor iutA, the salmochelin siderophore iroBCDN and truncated copies of genes encoding the capsular polysaccharide synthesis (CPS) regulators rmpA and rmpA2 ( Figure 1 A). According to previous studies, deletions of either rmpA or rmpA2 genes resulted in a significant decrease of CPS [ 9 , 10 , 38 ]. The presence of nonfunctional alleles of these genes might be the cause for the absence of the hypermucoviscous phenotype in isolate MS3802.…”
Section: Resultsmentioning
confidence: 99%